The Role of Purine Metabolites as DAMPs in Acute Graft-versus-Host Disease - Apostolova, Petya; Zeiser, Robert (Frontiers in Immunology, 2016)
Acute graft-versus-host disease (GVHD) causes high mortality in patients undergoing allogeneic hematopoietic cell transplantation (allo-HCT). An early event in the classical pathogenesis of acute GVHD is tissue damage caused by the conditioning treatment or infection that consecutively leads to translocation of bacterial products (pathogen-associated molecular patterns, PAMPs) into blood or lymphoid tissue, as well as danger-associated molecular patterns (DAMPs), mostly intracellular components which act as pro-inflammatory agents, once they are released into the extracellular space. A subtype of DAMPs are nucleotides such as adenosine triphosphate (ATP) released from dying cells that can activate the innate and adaptive immune system by binding to purinergic receptors. Binding to certain purinergic receptors leads to a pro-inflammatory microenvironment and promotes allogeneic T cell priming. After priming, T cells migrate to the acute GVHD target organs, mainly skin, liver and the gastrointestinal tract and induce cell damage which further amplifies the release of intracellular components. This review summarizes the role of different purinergic receptors in particular P2X7 and P2Y2 as well as nucleotides in the pathogenesis of GVHD.